The Participation of a Malignant Catarrhal Fever Virus and Mycoplasma bovis in the Development of Single and Mixed Infections in Beef and Dairy Cattle With Bovine Respiratory Disease - Oliveira, Thalita Evani Silva; Scuisato, Gabriela Sanches; Pelaquim, Isadora Fernanda; Cunha, Cristina Wetzel; Cunha, Lucas Santana; Flores, Eduardo Furtado; Pretto-Giordano, Lucienne Garcia; Lisbôa, Júlio Augusto Naylor; Alfieri, Amauri Alcindo; Saut, João Paulo Elsen; Jorge da Cunha, Paulo Henrique; Headley, Selwyn Arlington (Frontiers in Veterinary Science, 2021)
The bovine respiratory disease (BRD) complex is a multietiological and multifactorial disease associated with a wide range of viral and bacterial pathogens. This study evaluated the contribution of specific infectious disease agents in the development of BRD in cattle from Brazil and determined if a virus within the malignant catarrhal fever virus (MCFV) group and Mycoplasma bovis, acting individually or in conjunction, can be associated with the development of BRD. Formalin-fixed paraffin-embedded pulmonary sections were used in immunohistochemical assays to determine the intralesional presence of six antigens associated with BRD: bovine alphaherpesvirus 1 (BoHV-1), bovine parainfluenza virus 3 (BPIV-3), bovine viral diarrhea virus (BVDV), bovine respiratory syncytial virus (BRSV), MCFV, and M. bovis. Pneumonia was diagnosed in 82.7% (120/145) of all cattle evaluated. Interstitial pneumonia (60%, 72/120) and suppurative bronchopneumonia (25.8%, 31/120) were the most frequent patterns of pneumonia identified. Intralesional antigens of MCFV (53.3%, 64/120) were the most frequently associated with BRD, followed by M. bovis (47.5%, 57/120), BVDV (42.5%, 51/120), BoHV-1 (28.3%, 34/120), BRSV (24.2%, 29/120), and BPIV-3 (8.3%, 10/120). Additionally, antigens of BVDV, MCFV, and M. bovis were the most frequently identified agents associated with singular and concomitant infections. The MCFV identified during this study is more likely to be ovine gammaherpesvirus 2 (OvHV-2), since OvHV-2 is the only MCFV identified within the geographical region of this study. Interstitial pneumonia with proliferative vascular lesions may be a useful histologic feature to differentiate MCFV-induced pneumonia from other viral pneumonias of cattle. These results demonstrate that MCFV and M. bovis, in single or mixed infections, can produce pneumonia in cattle and should therefore be considered as primary agents in the development of BRD.